Allah Mencari Manusia Berdosa: Sebuah Analisa Sastra Teks Kejadian 3:8-19 - Kristiawan, Ragil (Jurnal Teologi dan Pelayanan Kerusso, 2024)
Genesis chapter 3 narrates the entry of sin into the world and its consequence, original sin, for all of humanity. Amid this darkness, there is a glimmer of hope in the narrative, as God actively seeks out sinful humanity. This study aims to examine God's response to humankind after the fall into sin. Utilizing a qualitative literature study method, this research conducts a literary analysis of Genesis 3:8-19. The analysis includes translating the BHS text, constructing the text’s structure, character analysis, literary structure, and examining the dramatic flow of the text. The literary analysis yields three key findings. First, it is God who takes the initiative to seek out humanity after the fall into sin. God’s role as the protagonist in this narrative serves as key evidence of His desire to communicate with and save fallen humanity. The context of the fall and God's initiative to approach humanity underscores His pivotal role as the protagonist in this story. Second, while God seeks out sinners, His discipline still applies to those who violate His commands. This is clearly reflected in the dramatic structure intentionally crafted by the biblical author. Third, God takes the initiative to provide a solution to the problem of sin. The enmity established by God between the serpent and the offspring of the woman indicates His effort to deliver humanity from the bondage of sin.